Contributing to energy sustainability: a review of mesoporous material supported catalysts for Fischer–Tropsch synthesis. Issue 1 (27th November 2020) - Okonye, Leonard Uchejim; Yao, Yali; Hildebrandt, Diane; Meijboom, Reinout
Abstract : Utilization of mesoporous materials to enhance structure–performance relationship of Fischer–Tropsch catalysts. Abstract : Fischer–Tropsch synthesis (FTS) provides an alternative route for the conversion of carbon-containing feedstocks, such as biomass and municipal waste, to valuable end products. The concern, however, is how to make the process more efficient in terms of the activity of the catalyst and selectivity to desired products and in this way provide an economically competitive and sustainable technology to supply fuels and chemicals to global energy suppliers. This review centres on the optimisation of metals and the use of mesoporous materials to enhance the structure–performance relationship of catalysts used in FTS. The enhancement takes advantage of active site accessibility, increased surface-to-volume ratios and improved chemical potential, to facilitate optimum catalyst performance, therefore improving the entire process and minimising CO2 emissions. The unique properties of nanoparticles and mesoporous materials, higher volumetric activity, the controllability afforded by morphology modification of mesoporous materials and the various oxidation states of mesoporous metal oxides can be exploited for catalyst development.